Quasi-convex univalent functions - K. Inayat Noor; D. K. Thomas (International Journal of Mathematics and Mathematical Sciences)
In this paper, a new class of normalized univalent functions is introduced. The properties of this class and its relationship with some other subclasses of univalent functions are studied. The functions in this class are close-to-convex.